Breastfeeding as a balancing act - pregnant Swedish women's voices on breastfeeding - Karin Cato; Sara M. Sylvén; Helena Wahlström Henriksson; Christine Rubertsson (BMC, 2020)
Abstract Background Breastfeeding provides health benefits to both women and children. The rationale behind an individual woman's decision to breastfeed or not can depend on several factors, either independently or in combination. The aim of the current study was to explore attitudes towards breastfeeding among pregnant women in Sweden who intend to breastfeed. Methods Eleven mothers-to-be, one of whom had previous breastfeeding experience, participated in the study. The women were interviewed either by telephone or face-to-face during late pregnancy, with the aim of exploring their attitudes towards breastfeeding. A semi-structured interview-guide was used, and the transcripts of the interviews were analyzed using thematic analysis. The social ecological model of health is the theory-based framework underpinning this study. The model provides a comprehensive approach to understanding the factors that influence breastfeeding intention. Results When interviewed during pregnancy, women described breastfeeding as a balancing act between societal norms and personal desires. The women perceived a societal pressure to breastfeed, however it was accompanied by boundaries and mixed messages. This perceived pressure was balanced by their own knowledge of breastfeeding, in particular their knowledge of other women's experience of breastfeeding. When envisioning their future breastfeeding, the women made uncertain and preliminary plans, and negotiated the benefits and drawbacks of breastfeeding. There was a wish for individual breastfeeding support and information. Conclusions Pregnant Swedish women perceive their future breastfeeding as a balancing act between societal norms and personal desires. These findings suggest that while discussing breastfeeding during pregnancy, it could be of interest to collect information from pregnant women on their knowledge of breastfeeding and from where they have gained this knowledge, since stories from family and friends may make them question their own capacity to breastfeed. A thorough review of the woman's experiences and attitudes of breastfeeding is important in order to offer the best evidence-based breastfeeding support. Trial registration Ethical approval for the study was obtained from the Regional Ethical Review Board in Uppsala (Dnr: 2017/256).